The Relationship of Metaphors Used in Prose and Poetry Texts (In the Materials of English and Karakalpak Languages) (Eurasian Scientific Herald, 2023)
The article highlights the semantic possibilities of sadness metaphors, which are activated in the context of text derivation, and describes their use in poetic and prose texts.